Epibrassinolide impaired colon tumor progression and induced autophagy in SCID mouse xenograft model via acting on cell cycle progression without affecting endoplasmic reticulum stress observed in vitro - ÇOKER GÜRKAN, AJDA (My University, 2023)
© 2023 Elsevier LtdEpibrassinolide is a member of brassinosteroids with a polyhydroxysteroid structure similar to steroid hormones of vertebrates. It was shown that EBR decreased cell proliferation and induced apoptosis in different colon cancer cell lines without exerting a cytotoxic effect in epithelial fetal human colon cells. This finding highlighted the potential of epibrassinolide in clinical therapeutic setup. In our previous studies, we showed that epibrassinolide was able to induce apoptosis via endoplasmic reticulum stress. Recently, we also showed that endoplasmic reticulum and apoptotic stresses can be prevented via autophagic induction in non-cancerous epithelial or aggressive forms of cancer cells. Therefore, here in this study, we evaluated the anti-tumoral effect of epibrassinolide as well as the autophagy involvement in the aggressive forms of colon cancer cell lines as well as in vivo SCID mouse xenograft colon cancer model for the first time. For this purpose, SCID mouse model was used for subcutaneous injection of colon cancer cells in matrigel formulation. We found that autophagy is induced in both in vitro and in vivo models. Following tumor formation, SCID mice were treated daily with increasing concentrations of epibrassinolide for two weeks. Our findings showed that EBR inhibited the volume and diameter of the tumor in a dose-dependent manner by causing cell cycle arrest. Therefore our data suggest that epibrassinolide exerts a cytostatic effect on the agrressive form of colon cancer model in vivo, without affecting endoplasmic reticulum stress and the induction of autophagy might have role in this effect of epibrassinolide.
Keywords: Tıp; Histoloji-Embriyoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Histology and Embryology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); HÜCRE BİYOLOJİSİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; CELL BIOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Biyokimya; Hücre Biyolojisi; Biochemistry; Cell Biology; Apoptosis; Autophagy; Cell cycle; Colon cancer; Epibrassinolide; SCID mouse; Epibrassinolide; Colon cancer; SCID Mouse; Autophagy; Apoptosis; Cell cycle